Exploring lecturers’ experiences in developing EFL material at English Education Department in Three Different Universities - Sahril Nur; Samsudin Samsudin; Syauqiyah Awaliyah Alfiani Nur; Waode Ade Sarasmita Uke (Journal of English Language Studies, 2022)
This study aims at exploring the lectures’ way to develop EFL materials; strategies for developing EFL materials; and challenges in developing ELT Material. This study was conducted in English Education Department of three different universities namely STKIP Paracendekia Sumbawa, Makassar State University, and Halu Oleo University. In collecting the data, the researchers used narrative case study design. The instrument of this study was the researchers themselves. The result showed that firstly the lecturers who developed English material only implemented some steps in developing teaching material such exploring students’ need, contextualizing material, and use the material in teaching and learning process. In this case, the material developer disregarded some other steps such as material trials in small group and evaluation of teaching material. Secondly, the strategies used by the lecturers in developing teaching material is by using analysis, Imitation, and modification, determining the aim of developing teaching material, knowing the number of students and time duration is available, and team teaching. Lastly, in developing teaching materials, the lecturer found some challenges such as difficulties of finding text and sources based on local wisdom, appropriated material, changeable lesson plan, and cost and time